Studying the plant element on Sheikh Saleh Al Ali Street and improving it virtually using modern software (Journal of Hama University, 2024)
This study was conducted in Sheikh Saleh Al-Ali, which extends from the University Tunnel to Al-Thawra Roundabout, with a length of 1.9 km, which is considered one of the most important and busiest streets in Latakia in 2022. The research aimed to study the actual reality of the tree element on Sheikh Saleh Al-Ali Street and improve it virtually through modern software. The results of the research showed that there was a suitable plant diversity in the street, with the percentage of fan palm (49.50%), jacaranda (27.10%), and the lowest percentage of camel moccasin (0.82%).Some distortions were found in the growth of street trees, including the inclination of the trunk on the plumb line, a decrease in the vertical space of the crown, as the average vertical space for some trees reached (1.6 m), and the distance between trees, lighting poles, and traffic, advertising, and directional signs was appropriate on both sides of the street. The research also presented a model Three-dimensional enhancer of the studied street using modern computer software.
Keywords: street trees, urban forests, engineering elements, service elements, Lattakia.